Strategy for Improving Quality of Basic Health Services in Selayar Regency - Dedy Herianto; Syaharuddin Syaharuddin (Jurnal Ilmiah Ilmu Administrasi Publik, 2020)
Various efforts in improving the quality of life of public health carried out by local governments have not been effective. The quality of health services in the islands of Selayar Regency is constrained by problems of access, the number of health workers and health facilities. This research method consists of the design of this study using qualitative designs. Data collection was carried out by the method of observation, interviews and documentation. Informants included officials and employees of the health department, health workers at the puskesmas, and the community. Data analysis consists of data reduction, data presentation and drawing conclusions. The results showed that in accordance with the three elements of the strategy dimension, namely objectives, policies, and programs, it could be categorized that the strategy to improve the quality of basic health services in the Selayar regency islands identified was strategy as a plan. Because the strategy as a plan has two basic characteristics, namely to accelerate the actions they will implement to implement programs to improve the quality of basic health services through the Regional Health System policy. And, develop consciously and full of purpose. One of them is by increasing the number of human resources for medical, non-medical and support staff. In addition to improving the quality of health facilities at the primary level (Community Health centers) and trying to maintain the availability of medicines at the health facilities. The problem that is still difficult to overcome is the accessibility of referral health services for people living in the outer islands of Selayar Regency.